2004
DOI: 10.1021/pr034084x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Peptide Affinity (SPA) System for the Identification of Mammalian and Bacterial Protein Complexes

Abstract: A vector system is described that combines reliable, very low level, regulated protein expression in human cells with two affinity purification tags (Sequential Peptide Affinity, or SPA, system). By avoiding overproduction of the target protein, this system allows for the efficient purification of natural protein complexes and their identification by mass spectrometry. We also present an adaptation of the SPA system for the efficient purification and identification of protein complexes in E. coli and, potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
197
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(198 citation statements)
references
References 18 publications
1
197
0
Order By: Relevance
“…To this end, sequential peptide affinity (SPA)-tagged DprA [i.e., harboring a C-terminal Flag epitope separated from a calmodulin-binding domain by a cleavage site for the TEV protease (19)] was ectopically expressed under the control of a competence-inducible promoter (Materials and Methods). The resulting ectopic construct was found to complement fully the transformation defect of a dprA-null mutant strain, demonstrating that the DprA-SPA fusion is functional.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, sequential peptide affinity (SPA)-tagged DprA [i.e., harboring a C-terminal Flag epitope separated from a calmodulin-binding domain by a cleavage site for the TEV protease (19)] was ectopically expressed under the control of a competence-inducible promoter (Materials and Methods). The resulting ectopic construct was found to complement fully the transformation defect of a dprA-null mutant strain, demonstrating that the DprA-SPA fusion is functional.…”
Section: Resultsmentioning
confidence: 99%
“…The mutated MCM-BP was then subcloned between the XbaI and NotI sites in pMZS3F (Zeghouf et al, 2004) using standard PCR protocols. The negative control plasmid for rescue experiments was pMZS3F with lacZ cDNA inserted between the XhoI and NotI sites.…”
Section: Methodsmentioning
confidence: 99%
“…The protein is predicted to contain an N-terminal TM helix (11,13), and previous subcellular localization experiments have shown that tagged derivatives partition with the membrane fraction and that the C terminus is in the cytoplasm (13). Our group has used the sequential peptide affinity (SPA) tag (14) to observe the accumulation of multiple sprotein fusions (11). Because AcrZ-SPA is easily detected (11) and a strain producing the tagged derivative is phenotypically wild type in a cell envelope stress assay (15) as well as in the antibiotic sensitivity assays described below, AcrZ-SPA was a good candidate for biochemical approaches to identify interacting protein partners.…”
Section: Acrz-spa Copurifies With Components Of the Acrab-tolc Membranementioning
confidence: 99%